Kajian Pendidikan Tentang Perspektif Filosofis Islam Terkait Eksplorasi Kebenaran Objektif Dan Sumber Pengetahuan - Rukmana, Suci; Karim, Ahmad Ar Rasyid Nur; Sari, Herlini Puspika (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by education as a place where knowledge can be found, understood and passed on to future generations. So that every individual from all levels of society is always interested in finding the truth because truth is a source of knowledge. However, the concept of truth is often subjective and can be interpreted variously by individuals or groups. This article describes the relationship between knowledge and truth in the philosophy of Islamic education. Through the process of exploring the truth with a rational basis of knowledge, humans are able to achieve objective and scientifically based understanding. The method used is library research with a qualitative type of research involving collecting information from various sources, such as books, articles and journals. Truth in Islam is often considered the pinnacle of true knowledge. Knowledge that is recognized as true is in accordance with religious teachings and brings humans closer to a true understanding of God, the universe and life. Islam views that correct knowledge must be in harmony with the truth contained in Islamic teachings, namely in accordance with the Al-Qur'an and hadith, and based on revealed religious teachings. Knowledge that is considered true in Islam is not just information that can be verified empirically, but also that which is rooted in Divine teachings. Key words: truth, knowledge, education